MENGUNGKAP METODE PENDIDIKAN DALAM PERSEPKTIF AL-QUR’AN DAN APLIKASINYA DI PONDOK PESANTREN AL-MUNAWWARAH DI KOTA PEKANBARU - Syahril Ramli; Munzir Hitami (An-Nida', 2018)
The position of al-Qur'an as the main source of Islamic education invites expert participation to explore its contents more deeply to realize this. It requires a method that can extract from the Qur'an, so that it can become a foothold in the theory and practice of Islamic education. One method that can be implemented is the tarbawi interpretation method, namely the method of studying the Qur'an with an Islamic education approach. The nuances of education in al-Qur'an are three arguments, namely the first many verses of the Qur'an can be found in the expression tarbiyyah (education). Secondly, the Prophet (SAS) identified himself as a Muslim (educator). Third, al-Qur'an teaches Muslims about life, so that the principles of the Qur'an must be a soul and guide for Islamic education. This research is a qualitative descriptive study, then supported by literature data that is related to this writing. The data is collected and classified according to the group. The author uses primary and secondary sources related to the object of study. The purpose of this study is to uncover the educational methodology in the perspective of the Koran and its application in the al-Munawwarah Islamic boarding school in the city of Pekanbaru (Analysis of thematic interpretations of al-Hikmah, al-Mau'izah and al-Mujadalah. Based on the results of the research conducted, the author found the word al-Hikmah in al-Qur'an 19 verses, the word al-Mau'izhah 9 verses and the word al-Mujadalah as many as 5 verses Indicators of the meaning of al-Hikamah: Wisdom, correct and firm words, knowledge , understanding, revelation of Allah (al-Qur'an), as-Sunnah and Hujjah (Arguments with words that are always based on the correct proposition to eliminate doubts and obtain truth. And indicators of the meaning of al-Mau'izhah: Advice, remind, subtle words, heartfelt descriptions / tenderness in giving advice, good lessons and teaching, and indicators of the meaning of al-Mujadalah: Good debate, dialogue, and exchange of thoughts / al-Munazharah. these three concepts have been applied in the learning process at the boarding school al-Munawarah in the city of Pekanbaru